Islam in post-Soviet Uzbekistan the morality of experience - Rasanayagam, Johan (Cambridge University Press, 2011)
"In recent years, the Uzbekistan government has been criticized for its brutal suppression of its Muslim population. This book, which is based on the author's intimate acquaintance with the region and several years of ethnographic research, is about how Muslims in this part of the world negotiate their religious practices despite the restraints of a stifling authoritarian regime. Fascinatingly, the book also shows how the restrictive atmosphere has actually helped shape the moral context of peoples' lives, and how understandings of what it means to be a Muslim emerge creatively out of lived experience"-- Provided by publisher